The ThioredoxinT and deadhead gene pair encode testis- and ovary-specific thioredoxins in Drosophila melanogaster. - Svensson, M.J.; Chen, J.D.; Pirrotta, V.; Larsson, J. (Chromosoma, 2003)
So far, two thioredoxin proteins, DHD and Trx-2, have been biochemically characterized in Drosophila melanogaster. Here, with the cloning and characterization of TrxT we describe an additional thioredoxin with testis-specific expression. TrxT and dhd are arranged as a gene pair, transcribed in opposite directions and sharing a 471 bp regulatory region. We show that this regulatory region is sufficient for correct expression of the two genes. This gene pair makes a good model for unraveling how closely spaced promoters are differentially regulated by a short common control region. Both TrxT and DHD proteins are localized within the nuclei in testes and ovaries, respectively. Use of a transgenic construct expressing TrxT fused to Enhanced Yellow Fluorescent Protein reveals a clear association of TrxT with the Y chromosome lampbrush loops ks-1 and kl-5 in primary spermatocytes. The association is lost in the absence of the Y chromosome. Our results suggest that nuclear thioredoxins may have regulatory functions in the germline.